PENGARUH DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI (Studi kasus Pada Pusat Penelitian Kebijakan Pendidikan dan Kebudayaan Kementerian Pendidikan dan Kebudayaan) - Hikmah, Hemmy (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2018)
The purpose of this research was to find out the influence of work discipline andcompetence partially and simultaneously on employee performance. This research usingquantitative research methods with techniques od data collecting through spreading of questionerand supported secondary data. Data analysis method used is multiple linear regression analysis.With resoult of data processing data using SPSS 24. The sample in this research is a proportionatestratified random sampling. The number of samples is 86 respondents from employees of PusatPenelitian Kebijakan Pendidikan and Kebudayaan (Puslitjakdikbud). The resultsof this researchshow that the variables of work discipline and competence partially and simultaneously have asignificant influence on the performance of employees of Pusat Penelitian Kebijakan Pendidikanand Kebudayaan (Puslitjakdikbud). Employee performance variables can be explained by thevariables work discipline and competence by 61,2%. While the remaining at 33,8% is explained byother variables not included in this research.